A new species of Mathevotaenia (Cestoda, Anoplocephalidae) parasitizing Tropidurus spinulosus (Reptilia, Squamata) from northeastern of Argentina. - Lía Inés Lunaschi; Matías Fernando Lamas; Fabiana Beatriz Drago (Revista Mexicana de Biodiversidad)
Mathevotaenia chaquensis n. sp. (Cestoda, Anoplocephalidae, Linstowiinae) from a Spiny Lava Lizard, Tropidurus spinulosus, collected in Chaco Province, Argentina, is described. This is the second species of Mathevotaenia described from Neotropical reptiles. The new species is principally characterized by having a relatively small strobila, 24 mm in total length, with about 100 craspedote proglottids, and 19-24 testes per proglottid. Among the South American species of Mathevotaenia, Mathevotaenia argentinensis is most similar to the new species by having similar body length and number of testes, but the major differences between both species include the size of suckers, neck, proglottids, testes and egg capsules, and the shape of the genital atrium and ovary (with 10-13 lobules on each side in M. argentinensis, and 4-7 lobules in M. chaquensis n. sp.).